Growth and production of South Sulawesi local waxy corn genotypes (Zea mays ceratina L.). Issue 1 (April 2020) - Syaiful, S A; Riadi, M; Mustaman, F A; Amin, A R; Farid, M; Mollah, A; Makmur,
Abstract: The study was conducted in the Experimental Farm of the Indonesian Cereals Research Institute (ICERI) located in the Gowa Regency, South Sulawesi Province from September to December 2017. The research aimed to study the quantitative and qualitative characters of some local waxy corn genotypes in South Sulawesi. This experiment was arranged in Randomized Block Design with three replications. The treatment included 9 local waxy corn genotypes from Barru, Bone, Bulukumba, Gowa, Jeneponto, Maros, Soppeng, Takalar, Wajo regencies and URI variety as a control. Local waxy corn genotypes of Bone and Bulukumba has the best phenotype characteristics with the highest grain yield (4.13 t/ha and 4.15 t/ha). Qualitative characters that are easily observed among different local waxy corn genotypes are panicle type, silk color (pistils), and kernel type. All the characteristics have high heritability (>0.50). Silking, weight of dry cob without husk, and cob diameter are the characteristics that give direct effect on the production positively (1.05; 0.001; 0.49, respectively).